The New Science of Communication : Reconsidering McLuhan's Message for our Modern Moment - Wachs, Anthony M., 1983- (Book collections on Project MUSE., 2015)
"A reading of Marshall McLuhan's work on media and technology that details the connection between his views on technology, media, and communications, and the classical arts of grammar, logic, and rhetoric, thereby restoring classical and medieval communication theory as an alternative to modern rationalist theories"--